Production of a mouse hybridoma secreting monoclonal antibody highly specific to hemoglobin Bart's (γ4) - Luksana Makonkawkeyoon (2018)
Hemoglobin (Hb) Bart's (γ4) was isolated and purified from Hb Bart's hydrops fetalis syndrome blood by CM-Sephadex C-50 chromatography. The isolated Hb Bart's was analyzed for its purity by high performance liquid chromatography. Balb/c mice were immunized intraperitoneally with Hb Bart's. The immunized mouse splenic cells were hybridized with mouse myeloma, X63-Ag8.653, by polyethylene glycol. There were 12 hybridoma clones, out of several thousand culture wells, secreting antibody against purified Hb Bart's. However, when those 12 monoclonal antibodies (mAb) were tested with Hb Bart's (γ 4), HbF (α2γ2), HbH, HbE, and HbA2, there was only 1 hybridoma clone secreting mAb highly reactive to Hb Bart's with very low reactivity to HbF. A rabbit polyclonal antibody with relative high reactivity to Hb Bart's compared to HbF with the ratio of 2.4:1 was also produced by affinity column chromatography for the purpose of developing an enzyme-linked immunosorbent assay (ELISA) base for qualitative and quantitative determination of Hb Bart's in adult hemolysates. Preliminary results in quantitative determination of Hb Bart's in Hb solution of 3 α thalassemia families having at least 1 child with HbH disease and 6 normal subjects indicated that it was possible to quantify Hb Bart's by our developed ELISA with appropriate sensitivity and specificity. © 2006 Carden Jennings Publishing Co., Ltd.